Case Report: Three Rare Cases of Ectopic ACTH Syndrome Caused by Adrenal Medullary Hyperplasia - Cheng, Yu; Li, Jie; Dou, Jingtao; Ba, Jianming; Du, Jin; Zhang, Saichun; Mu, Yiming; Lv, Zhaohui; Gu, Weijun (Frontiers in Endocrinology, 2021)
Ectopic ACTH syndrome (EAS) accounts for 10–20% of endogenous Cushing’s syndrome (CS). Hardly any cases of adrenal medullary hyperplasia have been reported to ectopically secrete adrenocorticotropic hormone (ACTH). Here we describe a series of three patients with hypercortisolism secondary to ectopic production of ACTH from adrenal medulla. Cushingoid features were absent in case 1 but evident in the other two cases. Marked hypokalemia was found in all three patients, but hyperglycemia and osteoporosis were present only in case 2. All three patients showed significantly elevated serum cortisol and 24-h urinary cortisol levels. The ACTH levels ranged from 19.8 to 103.0pmol/L, favoring ACTH-dependent Cushing’s syndrome. Results of bilateral inferior petrosal sinus sampling (BIPSS) for patient 1 and patient 3 confirmed ectopic origin of ACTH. The extremely high level of ACTH and failure to suppress cortisol with high dose dexamethasone suppression test (HDDST) suggested EAS for patient 2. However, image studies failed to identify the source of ACTH secretion. Bilateral adrenalectomy was performed for rapid control of hypercortisolism. After surgery, cushingoid features gradually disappeared for case 2 and case 3. Blood pressure, blood glucose and potassium levels returned to normal ranges without medication for case 2. The level of serum potassium also normalized without any supplementation for case 1 and case 3.The ACTH levels of all three patients significantly decreased 3-6 months after surgery. Histopathology revealed bilateral adrenal medullary hyperplasia and immunostaining showed positive ACTH staining located in adrenal medulla cells. In summary, our case series reveals the adrenal medulla to be a site of ectopic ACTH secretion. Adrenal medulla-originated EAS makes the differential diagnosis of ACTH-dependent Cushing’s syndrome much more difficult. Control of the hypercortisolism is mandatory for such patients.